2016
DOI: 10.1155/2016/7917343
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Analysis of the Infraorbital Foramen: The Clinical Relevance

Abstract: The present study was conducted to ascertain the shape, size, presence of accessory foramina, direction, and the precise position of the infraorbital foramen (IOF) in relation to the inferior orbital margin (IOM), anterior nasal spine (ANS), nasion (Na), maxillary teeth, and supraorbital foramen/notch (SOF/N) in adult skulls in a Sri Lankan population. Fifty-four skulls (42 males and 12 females) were analyzed. The IOF was oval in shape (38.6% and 36.3% on the right and left side, resp.) in a majority of skulls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 21 publications
6
33
0
Order By: Relevance
“…The present study was reported that mean distance between infraorbitol foramen and anterior nasal spine was 35.51+3.75mm, this findings are in correlation with previous studies [16,17]. In another study also reported slight higher results than present study in Indian population [1]. The mean distance of the infraorbital foramen from the piriform aperture was 19.35+3.26mm, which was close to some previous studies record.…”
Section: Measurement Of Iofsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study was reported that mean distance between infraorbitol foramen and anterior nasal spine was 35.51+3.75mm, this findings are in correlation with previous studies [16,17]. In another study also reported slight higher results than present study in Indian population [1]. The mean distance of the infraorbital foramen from the piriform aperture was 19.35+3.26mm, which was close to some previous studies record.…”
Section: Measurement Of Iofsupporting
confidence: 92%
“…The infraorbital nerve block is widely used to accomplish regional anaesthesia during surgeries involving the midface region and paranasal sinuses. Traumatic or iatrogenic injury to the infraorbital neurovascular bundle may result in bleeding and hypoesthesia or paraesthesia or anaesthesia in the region of its supply [1][2][3][4]. The nerve block of infraorbital nerves can be used in following cases.…”
Section: Introductionmentioning
confidence: 99%
“…Dagistan et al also showed that the oval shape is the most common shape present in 58% of the cases [19]. Similarly, the oval shape was the most common shape in a Sri Lankan study [11]. In our study, however, the circular shape was the most common shape present in 54.8% of the cases.…”
Section: Discussionsupporting
confidence: 65%
“…Thus, it is essential for surgeons and anesthesiologists to have exact knowledge of the location of the IOF before any procedure [12]. Various anatomic landmarks are used in several studies to identify its location and help surgeons in reconstructive and orthognathic surgeries, as well as while performing a nerve block [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation